Use of lidocaine associated with bicarbonate as a strategy to reduce pain and discomfort in anesthetic procedures: a comprehensive review - de Lacerda, Dhiego Alves; Lima, Larissa Luana Lopes; Honorato, Pedro Fechine; Vale, Renata Braga; das Neves, Diego Formiga; de Sá Filho, Claudenor Pinho; de Moura, Thiago Quirino; Figueiredo, Vinícius Costa; de Oliveira, Anaylle Vieira Lacerda; Isidório, Ubiraídys de Andrade (Revista Sistemática, 2024)
Lidocaine is a local anesthetic that is widely used in medical and dental procedures due to its effectiveness and rapid analgesic action. However, its use may be associated with side effects such as pain at the time of injection and a burning sensation during administration. A common strategy to mitigate these adverse effects is the association of lidocaine with sodium bicarbonate, aiming to raise the pH of the anesthetic solution. This article reviews the most relevant studies on the use of lidocaine associated with bicarbonate as a strategy to reduce pain and discomfort in anesthetic procedures.